1966
DOI: 10.1002/ijc.2910010209
|View full text |Cite
|
Sign up to set email alerts
|

Increased glycolytic capacity and associated enzyme changes in BHK21 cells transformed with polyoma virus

Abstract: Of all the metabolic differences claimed to exist between normal and malignant tissue the most consistently reported is a higher glycolytic capacity in malignant cells (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1968
1968
1982
1982

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This increased transport of glucose is an early event in transformation (8) and may be related to the increased glycolytic flux that has been reported in transformed cells (3,(12)(13)(14)(15)(16)(17). In order to determine the relationship between this increased glycolytic flux and the enhanced sugar transport, and to identify the metabolic step(s) affected by transformation, we have examined the changes in activities of key glycolytic enzymes and also the changes in the levels of glycolytic intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…This increased transport of glucose is an early event in transformation (8) and may be related to the increased glycolytic flux that has been reported in transformed cells (3,(12)(13)(14)(15)(16)(17). In order to determine the relationship between this increased glycolytic flux and the enhanced sugar transport, and to identify the metabolic step(s) affected by transformation, we have examined the changes in activities of key glycolytic enzymes and also the changes in the levels of glycolytic intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…pH) which might also influence the tumour-cell metabolism. In particular, it has been demonstrated that the glucose consumption of tumour cells depends on the concentration of H+ ions in the surrounding medium (Zwartouw & Westwood, 1958;Paul et al, 1966;Bock & Frieden, 1976). Diffusion equations assuming consumption rates that are independent of the concentration of some of these substrates may, therefore, only yield a rough approximation to the actual distribution of these metabolites within spheroids.…”
mentioning
confidence: 99%
“…Thus, the ELD and ELT cells propagated in vitro GLUCOSE-6-PHOSPHATE DEHYDROGENASE showed much higher G-6-PDH activities than the same cells propagated in vivo as ascites tumors, but according to Biczowa et al (9) only small differences between the glycolytic activities of these cell lines can be demonstrated. The absence of a positive correlation between glycolysis and G-6-PDH activity in cultured celk was previously reported by Paul (8), who found that infection with polyoma virus may stimulate the glycolytic activity of hamster kidney cells (BHK 21) in culture and at the same time depress the G-6-PDH activity as measured per cell. Thus, even if a high rate of glycolysis often seems to be accompanied by a high G-6-PDH activity, no strict correlation has been demonstrated.…”
Section: Warsaw Polandmentioning
confidence: 60%